Analisis Kesalahan Berbahasa Teks Berita Dalam Website "Detiknews" Edisi Februari 2024 Sebagai Kalayakan Bahan Ajar Membaca Kritis Siswa Kelas X SMA Terhadap Perilaku Sosial Remaja - Allamanda Kusumaning Anjora; Deviani Ayu Suranto; Erika Anggraeni; Hesti Kurnianingtyas; Nafhisa Diva Salsabella; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
The development of the times is accompanied by progress in various fields of life, such as science, technology, and economics. Progress is also felt in the scientific field of journalism. One of the terms in the field of journalism that is commonly known by the general public is print mass media, such as newspapers. Today's newspapers are not only printed on paper, but many newspapers have created their own blogs or pages so that news can be read online. The aim of this research is to analyze language errors based on the classification of linguistic categories, namely syntax, which includes the areas of spelling and sentence effectiveness. The data source is several news stories published on the detikNews website in the February 2024 edition. The data was then analyzed using the listening method and note-taking techniques. The results of the research showed that there were 52 errors in the use of spelling and punctuation, which were described as follows: a) there were 11 errors in writing foreign words; b) there were 8 errors in writing numbers; c) there were 13 errors in writing capital letters; d) there were 15 errors in the use of punctuation marks; e) there were 5 errors in writing pronouns. Apart from that, there were 44 errors in the use of ineffective sentences, which are described as follows: a) there were 14 errors in choosing diction; b) there are 10 sentences with no subject or predicate; c) there are 9 sentences with overlapping words; d) there are 11 long-winded sentences. It is hoped that the results of the analysis in this article will increase understanding and deeper knowledge regarding linguistics, namely syntax, including the areas of spelling and word choice and their use, knowledge about the types, as well as providing suitable teaching materials for class X high school students for them to carry out assessments and considerations. about adolescent social behavior critically.